Selective production of monocyclic aromatic hydrocarbon from agricultural waste wheat straw for aviation fuel using Ni/ZSM-5 catalyst. (October 2022) - Pan, Hongling; Zhou, Xuan; Xie, Shuixiang; Du, Zhicai; Li, Guotao; Zhang, Chunquan; Luo, Yan; Zhang, Xuefeng
Abstract: Aromatic is a vital chemical raw material and product as well as an essential component for aviation fuel. Bio-based aromatics, especially the monocyclic aromatic hydrocarbon, are beneficial for the green chemical process and aviation fuel development. In this research, firstly, the effects of different kinds of metal catalysts (Pt/C, Rh/C, Ru/C, Pd/C, 65 wt% Ni/SiO2 –Al2 O3 ) on the pyrolysis behavior and aromatic hydrocarbons selectivity of four kinds of agricultural and forestry waste biomass (wheat straw, rape straw, poplar sawdust, and bamboo powder) were systematically investigated. The research results showed that the selectivity of aromatics has been largely increased in the presence of 65 wt% Ni/SiO2 –Al2 O3 while the carbon-based noble catalysts had few impacts on aromatics production. Furtherly, zeolite with different Si/Al ratios (5:18, 5:50, 5:85, 5:300, and 5:470) and the Ni loading amounts (5, 10, 15, 20, 25 wt%) were systematically studied. The series of Ni/ZSM-5 catalyst reduced the phenolic components in the pyrolysis products, and significantly increased the relative content of the target product aromatics, and the proportion of monocyclic aromatic hydrocarbons in the aromatic. The research results showed the ZSM-5 with the Si/Al ratio of 5:18 had the best catalytic properties for aromatic production. The loading of 10 wt% of Ni (10 wt% Ni/ZSM-5, Si/Al = 5:18) further boosted the catalytic performance for wheat straw, achieving the highest relative concentration of aromatic at 67%, of which the ratio of monocyclic aromatic hydrocarbon was 55%. Highlights: Agricultural and forestry wastes were pyrolyzed over Ni/ZSM-5 to produce high-value aromatics. ZSM-5 with the Si/Al ratio of 5:18 had the best catalytic properties for aromatic production. For wheat straw, the maximum relative content of monocyclic aromatic was achieved at 55% using 10 wt% Ni/ZSM-5.